The computation of the index of a Morse function at a critical point - Takis Sakkalis (International Journal of Mathematics and Mathematical Sciences)
A theoretical approach in computing the index of a Morse function at a critical point on a real non-singular hypersurface V is given. As a consequence the Euler characteristic of V is computed. In the case where the hypersurface is polynomial and compact, a procedure is given that finds a linear function ℓ, whose restriction ℓ|V, is a Morse function on V.